APAKAH REMITANSI MENURUNKAN KEMISKINAN DI INDONESIA? (PENDEKATAN AUTOREGRESSIVE DISTRIBUTION LAG) - Muslihatinningsih, Fivien; Hadi, Samsul; Istiyani, Nanik (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
One of the problems often faced in achieving community welfare is poverty. This study aims to analyze the effect of Remittances, Gross Domestic Product (GDP), Unemployment Rate, and Economic Crisis on poverty in Indonesia 1990-2022. The analysis method used is explanatory research with a quantitative approach regression analysis method using the Autoregressive Distribution Lag (ARDL) estimation tool. The data used is secondary data in the form of time series data from 1990 to 2022. Based on the conditional Error Correction Model (ECM) test, Remittances have a negative but insignificant influence in the long run and short run. Gross Domestic Product (GDP) has a negative and significant influence in the short run. However, in the long run GDP has a negative and insignificant influence. The unemployment rate has a positive and significant influence in the long run. However, in the short term the unemployment rate has a negative and insignificant effect. Economic crisis has a positive and significant effect in the long term. However, in the short term the economic crisis has no effect on poverty in Indonesia.